SERPINA 14 expression in cows with embryonic mortality and aborted - Risvanli, A.; Yuksel, M.; Bulut, H.; Seker, I.; Kul, S. (Wiley-Blackwell, 2014)
[Abstract Not Available]
18th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- SEP 11-13, 2014 -- Helsinki, FINLAND